The analysis of Blender open-source software cloth simulation capabilities - Kogut, Wojciech (Journal of Computer Sciences Institute, 2023)
This article explores Blender open-source software capabilities in the area of cloth simulations. Simulation performance with different scene complexity and quality settings is tested with a script that automates the testing. System resource utilization is measured and the appearance of visual artifacts is taken into consideration. Cloth simulation features of Blender are compared to commercial software.